Biofunctional plant fibers and their bioactive-based materials: A critical review - Mohammed Alsafran (11482987) (2025)
Plants have been a significant source of natural fiber since antiquity. In recent years, natural plants and their bioactive-based fibers have been gaining popularity in the biomedical field due to increasing environmental concerns about synthetic fibers. This is primarily attributed to their biocompatibility, biodegradability, and biofunctional properties. In this review article, recent literature on plant fibers, their bioactive compounds, and biofunctional properties is compiled, including information on plant fibers dyed with phytoextracts and their biomedical applications. Moreover, factors influencing the biofunctional properties of plant fibers are also briefly discussed. The biofunctional properties of plant fibers are primarily attributed to the components of plant fiber extractives, which range in amounts from 0.1 % to 15.3 %. These components mainly include polyphenols, including lignin, pigments, volatile organic compounds (VOCs), and other components. Antimicrobial activity is the most studied biofunctional property in natural plant fibers, followed by antioxidant, UV protective, and wound healing activities. To enhance the biofunctional properties of plant fibers, natural plant fibers such as bamboo and cotton have also been dyed with various bioactive phytoextracts. Altogether, natural bioactive plant fibers along with their bioactive-based materials, can offer additional therapeutic benefits compared to synthetic materials, which highlights their sustainable and promising applications in the healthcare industry. We believe that the information reviewed in this article helps to understand the current and future potential of biofunctional natural plants and their bioactive-based fibers in the biomedical field. Other Information Published in: Biocatalysis and Agricultural Biotechnology License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.bcab.2025.103652